2016
DOI: 10.3847/0004-637x/827/2/133
|View full text |Cite
|
Sign up to set email alerts
|

Star Formation and Feedback: A Molecular Outflow–prestellar Core Interaction in L1689n

Abstract: We present Herschel 1 , ALMA Compact Array (ACA), and Caltech Submillimeter Observatory (CSO) observations of the prestellar core in L1689N, which has been suggested to be interacting with a molecular outflow driven by the nearby solar type protostar IRAS 16293-2422. This source is characterized by some of the highest deuteration levels seen in the interstellar medium. The change in the NH 2 D line velocity and width across the core provides clear evidence of an interaction with the outflow, traced by the high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 60 publications
4
16
0
Order By: Relevance
“…Table 2. This detection coincides with the starless core L1689N from Lis et al (2016), while the closest known protostar is IRAS16293-2422, which lies outside of the area plotted. Figure 4 for the plotting conventions adopted.…”
Section: Scuba Core Concentrationsupporting
confidence: 67%
See 1 more Smart Citation
“…Table 2. This detection coincides with the starless core L1689N from Lis et al (2016), while the closest known protostar is IRAS16293-2422, which lies outside of the area plotted. Figure 4 for the plotting conventions adopted.…”
Section: Scuba Core Concentrationsupporting
confidence: 67%
“…Sadavoy et al (2010b) identified this starless core as one of only a handful in Ophiuchus, Taurus, Perseus, and Orion, that appear to be super-Jeans (having a mass of roughly twice the Jeans mass), and starless, and suggest it is a strong candidate for collapse. Lis et al (2016) also identified a source coincident with our detection using a combination of ALMA Compact Array and CSO observations, and list it as the starless core L1689N.…”
Section: Discussionmentioning
confidence: 63%
“…Multiple rotational transitions have also been detected using the Heterodyne Instrument for the Far Infrared (HIFI; de Graauw et al 2010) instrument on board the Herschel Space Observatory in the direction of high-mass star forming regions (Persson et al 2010;Gerin et al 2016) and with the Infrared Space Observatory (ISO; Ceccarelli et al 2002). The o-NH 3 (1 0 −0 0 ) has also been detected with Herschel by Codella et al (2010) toward the shock region L1157-B1, by Salinas et al (2016) toward the protoplanetary disk TW Hydrae, and by Lis et al (2016) in the direction of the starless core L1689N, next to the young protostar IRAS16293-2422. None of the above spectra show resolved hyperfine structure of o-NH 3 , including the one toward L1689N, where only one group of hyperfine components is detected.…”
Section: Introductionmentioning
confidence: 98%
“…Although the total number is still limited, interferometric observations in the dust continuum have been identifying further substructures within starless cores in nearby high-mass and low-mass cluster forming regions, such as ρ-Ophiuchus, Perseus, and Orion (e.g., Schnee et al 2010;Schnee et al 2012;André et al 2012;Nakamura et al 2012;Friesen et al 2014;Lis et al 2016;Kirk et al 2017;Ohashi et al 2018). For isolated low-mass star-forming clouds, such as Taurus, the dust continuum observations toward the innermost part of starless cores remain to be explored further by interferometers.…”
Section: Quest For Low-mass Prestellar Cores On the Verge Of Protostamentioning
confidence: 99%